Bimbingan Konsumsi Dalam Islam - Rahmi, Rahmi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
Human beings are made up of various elements, it’s kind of soul, mind, body and the heart. These elements have a relationship between each other. For example, human needs to eat, basically is not a stomach or physical needs only, however, in addition to an impact on physical strenght, eat also have an impact on the other body elements, such as soul, mind and the heart. Therefore, Islam requires every food that we eat should have benefit the whole elements of the body. Therefore, what is consumed must meet the essential needs of all elements of the body. The purpose of the essential is a positive association between consumption activity with structured activities from elements of the bodies themselves. If consumption resulting in dysfunction and even damage to one or several elements of the body, of course it is not a essential needs of human. Therefore, Islam expressly forbids the items which will bring harm to the man himself.